144k views
1 vote
Solve this radical equation:

Solve this radical equation:-example-1
User Kathelyn
by
5.8k points

2 Answers

2 votes

Explanation:

Given,


√(x + 11) - x = - 1

To Find:

  • Value of x

Solution:

Square both sides, then solve.


\rm \implies \: \: √((x + 11) ) {}^(2) = ( - 1 + x) {}^(2)


\implies \rm \: x + 11 = - (1 + x) {}^(2)


\rm \implies \: \: x + 11 = 1 - 2x + x {}^(2)


\rm \implies \: 1−2x+x {}^(2)=x+11


\rm \implies1+x {}^(2) −3x=11


\rm \implies1+x {}^(2) −3x−11=0


\rm \implies {x}^(2) - 3x - 10 = 0

Factor the LHS


\implies \rm \: (x - 5)(x + 2) = 0

Bring terms equal to 0, that is


\implies \rm(x - 5) = 0

  • Solve for x


\implies \rm \: x = 5+ 0 = \boxed 5

AND set x+2 equal to 0,


\rm\implies \: x + 2 = 0

  • Solve for x


\rm \implies \: x = - 2

So the possible two values are 5 & -2.

But, after plugging the values for verifying each,the most accurate is 5.

So, the value of x is 5.

User Pollirrata
by
5.7k points
5 votes

Answer:

x = 5

Explanation:

User Vijiy
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.